2021
DOI: 10.1186/s12904-021-00855-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single session of 30-min mindful breathing in reducing fatigue among patients with haematological cancer – a randomised controlled trial

Abstract: Background Patients with haematological cancer had considerable symptom burden, in which fatigue was the most prevalent. Almost 70% of haematological cancer patients reported fatigue. Methods We conducted a parallel-group, non-blinded, randomised control trial at the haemato-oncology unit of University Malaya Medical Centre, from 1st October 2019 to 31st May 2020. Patients included were ≥ 18 years, had histopathological diagnosis of haematological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The authors reported that distress tracking and guided meditations were among the most used functions within the app. In another study recruiting patients with a variety of hematological oncology diagnoses (13.8% with MM), patients were randomized to a single session of 30 min mindful breathing versus standard care and reported significantly less fatigue in the intervention group [ 107 ]. Bates and colleagues explored the impact of music therapy considered by some scholars in the context of mind–body medicine, while others categorize it independently among the art therapies discipline.…”
Section: Mind–body Medicinementioning
confidence: 99%
“…The authors reported that distress tracking and guided meditations were among the most used functions within the app. In another study recruiting patients with a variety of hematological oncology diagnoses (13.8% with MM), patients were randomized to a single session of 30 min mindful breathing versus standard care and reported significantly less fatigue in the intervention group [ 107 ]. Bates and colleagues explored the impact of music therapy considered by some scholars in the context of mind–body medicine, while others categorize it independently among the art therapies discipline.…”
Section: Mind–body Medicinementioning
confidence: 99%
“…Mindfulness decouples thalamusprecuneus and ventromedial prefrontal deactivation, effectively inhibiting onward transmission of nociceptive input (42). Mindfulness improves emotional and cognitive well-being in people with persistent pain mediated in part by functional alterations in the insula, amygdala, and hippocampus (35)(36)(37)(38)(42)(43)(44)(45)(46)(47)(48)(49)(50). Neuroplastic changes occur in the insula associated with interoception and a reduction in negative emotional responses to unpleasant sensations such as pain (40,51).…”
Section: Beneficial Effects Of Mindfulnessmentioning
confidence: 99%
“…The final study pool consisted of 69 studies, including 25 yoga studies , 29 psychosocial studies , and 15 mindfulness-based studies [118,[126][127][128][129][130][131][132][133][134][135][136][137][138][139]. The PRISMA selection flow chart is presented in Figure 1.…”
Section: Included Studiesmentioning
confidence: 99%